Urban conflictivity in Chalco, notes on a contemporary socio-anthropological problem/Conflictividad urbana en Chalco. Notas sobre una problemática socioantropológica contemporánea (Encuentros, 2019)
The study of conflicts between different actors of dynamics of urbanization has been a matter of interest for political science, sociology, demographic history and urbanism. In particular, it has been significant for this work to find, in the conceptualization of Victor Turner’s social drama, an opportunity for a specific anthropological framework to address urban conflictivities. This paper deals with the conflict between actors of a particular urban growth dynamic, construction of large-scale popular housing in metropolitan territories of the central zone of Mexico, particularly the case of an urban social interest set in the municipality of Chalco, State of Mexico, between 2005 and 2007. They were found in collective actions, the phases of the construction of a social drama, as well as through the search of newspaper references and observation in the field, were confirmed: a production policy of popular housing received negatively in a specific territory, citizen groups in resistance were identified, by coordinating both collective actions and discursivity on the metropolitan territorial problems. Issues that allow, on the one hand, to exemplify the adaptability of the conceptualization of Turner’s social drama in urban contexts, outside the ethnological tradition; on the other hand, to find in the generality of drama, the singular manifestations of actors interested in the project of population and urban growth in their immediate surroundings.Key words: City; rurality; urban set; social drama.